Hidden narratives; Personal albums from the KITLV collection and their captions - Ouwehand, Liesbeth (Wacana, Journal of the Humanities of Indonesia, 2019)
This article examines captions found in the various personal albums in the KITLV photo collection (Koninklijk Instituut voor Taal-, Land- en Volkenkunde / Royal Netherlands Institute of Southeast Asian and Carribean Studies). The article shows that two types of captions can be distinguished: descriptive or identifying and commentary or refective captions. These captions are an important part of the albums’ materiality and composition. Hence, captions turn the albums into autobiographical objects for both compiler and intended audiences. It is argued that photo albums and their image content should not be read separately from the captions either physically or digitally in image databases.